2020
DOI: 10.1101/2020.12.10.20244350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development And Performance Evaluation of A Rapid In-House ELISA for Retrospective Serosurveillance of SARS-CoV-2

Abstract: BackgroundIn the ongoing pandemic situation of COVID-19, serological tests can complement the molecular diagnostic methods, and can be one of the important tools of sero-surveillance and vaccine evaluation.AimTo develop and evaluate a rapid SARS-CoV-2 specific ELISA for detection of anti-SARS-CoV2 IgG from patient’s biological samples.MethodsIn order to develop the ELISA, three panels of samples (n=184) have been used: panel 1 (n=19) and panel 2 (n=60) were collected from RT-PCR positive patients within 14 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Immunoplate 96-well flat-bottom plate (Extra Gene, USA) was coated with different dilution (1:50, 1:100, and 1:200) 100 µL/ well of mouse SARS-CoV-2 NCP specific monoclonal antibody using coating buffer (sodium bicarbonate, pH >9) and incubated either overnight at 4°C or 37°C for an hour following our previously established ELISA methods [22,23]. The unbound…”
Section: Assay Plate Preparationmentioning
confidence: 99%
“…Immunoplate 96-well flat-bottom plate (Extra Gene, USA) was coated with different dilution (1:50, 1:100, and 1:200) 100 µL/ well of mouse SARS-CoV-2 NCP specific monoclonal antibody using coating buffer (sodium bicarbonate, pH >9) and incubated either overnight at 4°C or 37°C for an hour following our previously established ELISA methods [22,23]. The unbound…”
Section: Assay Plate Preparationmentioning
confidence: 99%
“…For SARS-CoV-2, several studies had reported the use of ELISA to detect antibodies against N protein of SARS-CoV and the sensitivity and specificity of such test ranged from 90 to 94%, and, above 97%, respectively ( Table 11 ) [202] , [203] . Compared to ELISA assay that was aimed to detect antibodies like IgG against the N protein of SARS-CoV-2 [202] , [203] , the use of ELISA test that was focused to detect antibodies against S protein of SARS-CoV-2 showed wide range values of sensitivity and specificity, according to the findings reported from various studies [199] , [204] , [205] , [206] , [207] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…For SARS-CoV-2, several studies had reported the use of ELISA to detect antibodies against N protein of SARS-CoV and the sensitivity and specificity of such test ranged from 90 to 94%, and, above 97%, respectively ( Table 11 ) [202] , [203] . Compared to ELISA assay that was aimed to detect antibodies like IgG against the N protein of SARS-CoV-2 [202] , [203] , the use of ELISA test that was focused to detect antibodies against S protein of SARS-CoV-2 showed wide range values of sensitivity and specificity, according to the findings reported from various studies [199] , [204] , [205] , [206] , [207] . Some studies showed that S protein-based ELISA test was less sensitive to detect IgG and IgA against SARS-CoV-2 (<70%) [206] , [207] while few other studies reported that such test was highly sensitive (at least 90%) to detect IgG, IgA, or IgM against the virus S antigen [199] , [204] , [205] , [208] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though nucleic acid detection has the advantages of earlystage sensitivity, high specificity, and easy operation, the accuracy of nucleic acid detection results needs to be comprehensively analyzed from influencing factors such as sample type, quality, experimental factors, kit performance, patient infection cycle, especially for difficult-to-diagnose cases, the accuracy of detection should be more strictly controlled 8 . Therefore, complementary serological immunoassays such as enzyme-linked immunosorbent assay (ELISA), lateral flow immunoassay (LFIA), and loop-mediated isothermal amplification (LAMP), rapid highthroughput flow-through membrane immunoassay (FMIA) are utilized nowadays for the pathogen detection, infection progression evaluation, and transmission dynamics analysis [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%